Strategi Internalisasi Nilai-Nilai Pendidikan Karakter di Madrasah NU dan Muhammadiyah - Amin, Moh Nasrul (Darajat: Jurnal Pendidikan Agama Islam, 2021)
Madrasah as one of the educational institutions that have an important role in the process of internalizing the value of character education for students. The implementation of character education in Indonesia cannot be separated from the educational institutions owned by NU and Muhammadiyah. The two large organizations have been around for a long time and prioritize the process of implementing character education. These implementation efforts are accompanied by ways, programs or strategies for internalizing the value of character education itself. This article tries to provide a description of the findings of the strategy for internalizing the values ​​of character education in NU and Muhammadiyah educational institutions, namely MTs Hidayatush Syibyan as an educational institution owned by NU and MTs Muhammadiyah 1 located in Palang sub-district. Which in the process of internalizing values, MTs Hidayatush Sybyan does it through a habituation approach or approach to learning activities and extracurricular activities, exemplary of a teacher, direction and guidance, cooperation with parents of students, and finally through the enforcement of madrasa rules. While the strategy for internalizing character education values ​​at MTs Muhammadiyah 1 is through a strategy of integrating character values ​​into the curriculum or all subjects, advice by leaders and teachers to students, civilizing madrasas, through student discipline, teacher example, and finally through habituation. Overall, the internalization of character values ​​at MTs Hidayatush Sybyan and MTs Muhammadiyah 1 was carried out optimally, and in the strategy there were few differences between the two, namely at MTs Hidayatush Sybyan there was a way of working with the guardians of students to supervise student behavior, while at MTs Muhammadiyah 1 there were advantages related to integrating character values ​​into religious and other lessons.